Pulsating curves of zero velocity for infinitesimal mass around oblate and triaxial rigid body of triangular equilibrium points in elliptical restricted three body problem - Singh, Nutan; Narayan, A. (International Journal of Advanced Astronomy, 2017)
This paper explore pulsating Curves of zero velocityof the infinitesimal mass around the triangular equilibrium points with oblate and triaxial rigid body in the elliptical restricted three body problem(ER3BP).
Keywords: Er3bp; Triaxiality; Dynamical System; Zero Velocity Curve; Triangular Points.